Evaluating the feasibility and acceptability of home-based isometric exercise and behaviour change for the management of hypertension: The HOME-FIT study protocol - Helen Llewellyn; Sarah Audsley; Paul Court; Angela Rodrigues; Eurico Wilhelm Neto; Gabriel Grizzo Cucato (PLoS ONE, 2026)
This protocol describes a pilot randomised controlled trial that aims to assess the feasibility and acceptability of a 24-week remotely delivered home-based isometric exercise and behaviour change intervention for adults with arterial hypertension (AH) characterised as ≥140/90 mmHg by European and UK guidelines. The study will also explore the potential effects of the intervention on office and ambulatory blood pressure (BP). Seventy participants diagnosed with AH and receiving pharmacological treatment will be recruited from Newcastle upon Tyne, United Kingdom. Participants will be randomised with minimisation for sex and mean office systolic BP (≤140 mm Hg vs > 140 mm Hg) to the intervention (n = 35) or control group (n = 35). The intervention group will undergo 12 weeks of remotely supervised isometric wall squat exercises, three times per week, and will receive advice based on a leaflet that follows UK recommendations for behaviour change, including weight management, diet, physical activity, salt intake, alcohol reduction, and smoking cessation. After that, they will be followed for an additional 12 weeks and will continue to receive further guidance to maintain the wall squat exercise and behaviour changes. The control group will receive similar advice to that of the intervention group, reinforcing the standard care recommendation. Primary outcomes for feasibility will be determined by screening, eligibility, recruitment, and retention rates at 12 and 24 weeks. Exercise adherence will be measured by the proportion of sessions completed. Behaviour change adherence will be self-reported via a questionnaire and assessed at 12 and 24 weeks. Participant acceptability will be determined through semi-structured interviews. Secondary outcomes include office and ambulatory BP measurements at baseline, 12 weeks, and 24 weeks. Findings will guide the development of a future large-scale trial to evaluate the effectiveness and cost-effectiveness of non-pharmacological hypertension management, addressing key gaps and supporting scalable, patient-centred care. ClinicalTrials.gov Registration Number: NCT07213479